Characterisation and classification of arecanut-growing soils of Karnataka - Vasundhara, R.; Prakash, N.B.; Anil Kumar, K.S.; Hegde, Rajendra (Journal of Plantation Crops, 2020)
The present investigation was carried out to characterise the soils of areca based cropping system considering soil type and agro-climatic variability. Ten typical soil profiles were studied representing five different agro-climatic zones (ACZs) of Karnataka, namely, Tumkur and Hesarghatta (Eastern Dry Zone), T. Narasipura and Maddur (Southern Dry Zone), H D Kote and Hassan (Southern Transition zone), Mudigere and Sirsi (Hilly Zone), and Belthangady and Kumata (Coastal Zone). These pedons were studied for their morphological characteristics, physical and physicochemical properties. The arecanut-growing soils of Karnataka are generally deep to very deep, non-gravelly and well-drained soils. Texture ranged from sandy clay loam to clay in sub-surface. Soils of coastal and hilly zones were strongly acidic and had high organic carbon. In contrast, other sites of the southern transition zone to southern and eastern dry zone soils were near neutral to moderately alkaline with medium to high organic carbon content. Cation exchange capacity (CEC) ranged 2.5 to 32.6 cmol (p+) kg-1 base saturation varied 21.9 to 99.6 per cent. The major taxa of the soils identified at sub-group level of soil taxonomy were Rhodic Kanhaplustalfs, Typic Haplustalfs, Rhodic Paleustalfs, Typic Rhodustalfs, Vertic Haplustepts, Typic Haplustepts, Ustic Kanhaplohumults, Kanhaplic Haplustults and Typic Paleustults.